A new functional role uncovered for RASGRF2 in control of nuclear migration in cone photoreceptors during postnatal retinal development. (2nd January 2017) - Jimeno, David; Santos, Eugenio
ABSTRACT: Despite their homologous structure and central nervous system(CNS) expression patterns, the GRF1 and GRF2 guanine nucleotide exchange factors(GEF) appear to play distinct, non-overlapping functions in cellular excitability, synaptic plasticity or neuromodulation. We recently uncovered a new functional role of GRF2 controlling nuclear migration in cone photoreceptors during postnatal neuroepithelial differentiation of the mouse retina. Analyzing GRF2-KO mice, we detected the specific accumulation of abnormally located, "ectopic" cone photoreceptor nuclei in the photoreceptor segment(PS) layer of their retinas. This alteration was accompanied by defective electroretinograms(ERG) indicative of impaired cone-mediated visual function, and accumulation around the "ectopic" nuclei of signaling molecules known to be functionally relevant for intracellular organelle migration, cytoskeletal reorganization or cell polarity establishment including PAR3, PAR6, and the phosphorylated proteins pPAK, pMLC2 and pVASP. We propose a mechanism whereby the absence of a productive functional interaction between GRF2 and its downstream target CDC42 leads to altered formation/structure of PAR-containing, polarity-related macromolecular complexes and abnormal activation of downstream signaling mediated by activated, phosphorylated forms of PAK, VASP and MLC2. As cone photoreceptors are responsible for color vision and visual acuity, these observations are potentially relevant for degenerative diseases of the human retina, harboring almost double number of cones than mice.